EXPLORATION OF INDIGENOUS ENDOPHYTIC ACTINOBACTERIA AS BIOCONTROL AGENTS AGAINST STEWART’S WILT (Pantoea stewartii subsp. stewartii) AND THEIR ROLE IN ENHANCING MAIZE GROWTH AND YIELD - Khomisatul Ahdaniah; Yulmira Yanti; Ujang Khairul (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2026)
Stewart’s wilt disease in maize is caused by the seed-borne bacterium Pantoea stewartii subsp. stewartii. The use of actinobacteria as biological control agents represents an environmentally friendly alternative for disease management, as these microorganisms can produce antagonistic secondary metabolites against plant pathogens. This study aimed to identify the best indigenous actinobacterial isolate for controlling Stewart’s wilt disease and improving the growth and yield of sweet corn. The research was conducted in two stages: (1) isolation and characterization of actinobacteria and P. stewartii subsp. stewartii, and (2) selection of indigenous actinobacteria for disease suppression and plant growth promotion. The experiment was arranged in a completely randomized design with 22 treatments and three replications. Observations included actinobacterial morphology, biosafety testing, disease development, and growth and yield parameters of sweet corn. A total of 25 actinobacterial isolates were obtained, of which five were pathogenic to maize based on biosafety tests. Isolate APPS1.4 showed the highest effectiveness by extending the incubation period to 8.98 days and reducing disease incidence and severity to 16.94% and 17.26%, respectively. Isolate APPS1.4 also increased plant height to 140,80 cm, leaf number to 10,70 leaves, and ear weight of sweet corn to 837,66 g.